Aadel Brun Tschudi Annual Lecture 2017 – efficiency and equity in development geography, the SDGs and the Sendai Framework. Issue 1 (1st January 2020) - Pelling, Mark
ABSTRACT: What can contemporary geographical research learn from Aadel Brun Tschudi? As a pioneer of development geography, Tschudi emphasised efficiency, equity and the responsibility of geographers to be active in society. While her contributions to development geography were made in the context of nation-building efforts in the mid–late 20th century, the globalising process of the early 21st century raise similar concerns for identity, emergent hierarchies of power and socio-environmental transformation. Using Tschudi's cardinal principles of equity and efficiency, the paper identifies four action arenas and exemplifies these through interventions aimed at reducing risk and addressing unmet development challenges: (1) high efficiency, low equity (private sector led), (2) low efficiency, low equity (humanitarian sector led), (3) low efficiency, high equity (spontaneous local action), and (4) high efficiency, high equity (collaborative action). The analysis draws out the different ways in which the aspirations and policy communities that own the United Nations' Sustainable Development Goals (SDGs) and the Sendai Framework for Disaster Risk Reduction 2015–2030 are interacting now and how far these interactions are able to deliver efficiency and equity for the poor in low- and middle-income countries, which is Tschudi's primary concern.